2019
DOI: 10.7759/cureus.5599
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Barriers Toward Research Among Medical Students of Karachi

Abstract: IntroductionOur study was meant to assess the knowledge, attitude, and barriers towards research in medical students of Pakistan. By assessing the factors, we aim to increase the role of medical students in research, which will eventually help developing countries like Pakistan to achieve self-reliance in health care.MethodsUndergraduate and postgraduate students of medicine, dentistry, and pharmacy schools of Dow University of Health Sciences, Karachi, were enrolled from February-March 2018 in a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 18 publications
3
35
0
2
Order By: Relevance
“…Research positively provokes analytical thinking and has a positive impact on career choice in medical students. 14 Unfortunately, little drift and interest is shown towards it mainly due to grueling hours of clinical practice, tough medical studies and little access to resources and lack of research mentors. 14 Only 6.6% of respondents agreed to pursue research in their future career.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research positively provokes analytical thinking and has a positive impact on career choice in medical students. 14 Unfortunately, little drift and interest is shown towards it mainly due to grueling hours of clinical practice, tough medical studies and little access to resources and lack of research mentors. 14 Only 6.6% of respondents agreed to pursue research in their future career.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Unfortunately, little drift and interest is shown towards it mainly due to grueling hours of clinical practice, tough medical studies and little access to resources and lack of research mentors. 14 Only 6.6% of respondents agreed to pursue research in their future career. This is probably due to lack of research orientation at undergraduate level.…”
Section: Discussionmentioning
confidence: 99%
“…These attitudes were also higher in comparison to the attitudes of medical students at Damascus University, which were captured in 2018 using the same tool of measurement (13). However, this contrasted with two studies from Iran and Pakistan that reported postgraduates to have had lower attitudes towards research than undergraduates (23,24). The reasons for that in the Syrian sample might have been that postgraduates were in daily contact with the uncertainties in disease management, the limitations of relevant guidelines, along with the limited resources as in Syria especially during the crisis (25).…”
Section: Discussionmentioning
confidence: 71%
“…The deficits in research, their correction as well as the need and benefits of integration of research experience into the medical curricula is reiterated in several papers. [ 31 32 ]…”
Section: Discussionmentioning
confidence: 99%